Jībane galpa āche - Datta, Jyotiprakāśa (Ityādi Grantha Prakāśa, 2010)
Dyūtakrīṛā – Jībane galpa āche, galpe jībana – Yādubāstabatāra galpa – Yadi keu phere – Jyoṯasnāra śarīre āche śoṇitera ghrāṇa – Nirāloka nagarī o sthirajale pārāpāra – Mepe dekho, jībana bātāse bhāse – Svapnacārī smr̥timaẏa – Kālakūṭa Stories on social themes
Short stories. - In Bengali-Schr
Keywords: Bengali; Kurzgeschichte; Geschichte 1900-2000